CFD modeling of spontaneous heating in a large-scale coal chamber - Liming Yuan (The National Institute for Occupational Safety and Health (NIOSH), 2009)
Three-dimensional computational fluid dynamics (CFD) modeling is conducted to simulate spontaneous heating in a large-scale coal chamber with a forced ventilation system. Spontaneous heating is modeled as the low-temperature oxidation of coal using kinetic data obtained from previous laboratory-scale spontaneous heating studies. Heat generated from coal oxidation is dissipated by convection and conduction, while oxygen and oxidation products are transported by convection and diffusion. The water vapor transfer and the effect of heat of wetting are not modeled. The CFD model is validated by comparing simulation results with test results from U.S. Bureau of Mines experiments conducted in the coal chamber. The model predicts lower temperatures in the early stage but agrees well on the induction time for spontaneous heating. The effects of airflow rate and order of reaction on the spontaneous heating process are also examined. The calibrated CFD model is found to be useful for predicting the induction time for spontaneous heating in underground coal mines.